Água residuária de suinocultura associada à adubação mineral No cultivo da soja: 18º ciclo - Pereira, Pâmela Aparecida Maldaner (2015)
18 Abstract: The reuse of water in agricultural soils is an ancient and promising effective 19 practice in the development of cultures and important water resources management tool. 20 The objective of this study was to evaluate the effects of continuous application of 21 swine wastewater in different doses, associated with mineral fertilizer, in eight years of 22 management in no-till system, about the chemical conditions of the soil and soybean. 23 The experiment was conducted in the field in typical Dystroferric Red Oxisol with a 24 very clayey texture. The wastewater doses of swine applied from the beginning in the experimental area were 0, 100, 200, 300 m3 ha-1 25 prior to the seeding, associated with the 26 presence and absence of mineral fertilizer. The results were submitted to normality tests, ANOVA and Tukey test. The dose of 100 m3 ha-1 27 of swine wastewater associated with 28 mineral fertilizer was efficient nutrition soybean requirements, without causing damage 29 to the soil. Attention should be paid to the possible accumulation of copper and zinc in 30 the soil over the years.